Introduction to the 10th Anniversary INSEN Special Issue - Matteo Gerlini; Russel K Hirst; Rachel Brooks (International Journal of Nuclear Security, 2020)
This IJNS special issue celebrates the first ten years of the International Nuclear Security Education Network (INSEN). A partnership between the International Atomic Energy Agency (IAEA) and the international academic community, INSEN was established in 2010 to promote nuclear security education. The articles in this issue focus on the shared education and training experiences of INSEN members in this new academic field of nuclear security. This special issue also features sketches of INSEN life provided by a number of its chairs, who share their thoughts and feelings about INSEN’s significance for the organization’s educators and leaders, and who chronicle the transformation of the network.